Era Ekonomi Berkelanjutan: Studi literatur tentang Gerakan Bisnis Berkelanjutan - Aryati Dinta Kusumaningrum; Dhian A. Safitra (Majalah Ilmiah Bijak, 2020)
At present, awareness of the importance of maintaining environmental sustainability is increasingly widespread. The global community has also realized that this earth does not belong to this generation alone. In each period, various kinds of movements were introduced to encourage sustainable development. But what exactly is the difference between these proposed movements? This research with the literature review method will identify sustainable business movements from 1990 to the present. From the results of existing identification, this study will recommend which movements are realistic to implement in Indonesia, which has a unique character than other countries in the world.